Molecular cloning and characterization of the glucoamylase gene of Aspergillus awamori. - Nunberg, J H (1984)
The filamentous ascomycete Aspergillus awamori secretes large amounts of glucoamylase upon growth in medium containing starch, glucose, or a variety of hexose sugars and sugar polymers. We examined the mechanism of this carbon source-dependent regulation of glucoamylase accumulation and found a several hundredfold increase in glucoamylase mRNA in cells grown on an inducing substrate, starch, relative to cells grown on a noninducing substrate, xylose. We postulate that induction of glucoamylase synthesis is regulated transcriptionally. Comparing total mRNA from cells grown on starch and xylose, we were able to identify an inducible 2.3-kilobase mRNA-encoding glucoamylase. The glucoamylase mRNA was purified and used to identify a molecularly cloned 3.4-kilobase EcoRI fragment containing the A. awamori glucoamylase gene. Comparison of the nucleotide sequence of the 3.4-kilobase EcoRI fragment with that of the glucoamylase I mRNA (as determined from molecularly cloned cDNA) revealed the existence of four intervening sequences within the glucoamylase gene. The 5' end of the glucoamylase mRNA was mapped to several locations within a region -52 to -73 nucleotides from the translational start. Sequence and structural features of the glucoamylase gene of the filamentous ascomycete A. awamori were examined and compared with those reported in genes of other eucaryotes.